PENGARUH PERBANDINGAN TEPUNG BERAS DENGAN PASTA UBI JALAR UNGU (Ipomoea batatas L. Poir) TERHADAP KARAKTERISTIK CENDOL - Wulandari, Putri Ayu; Sugitha, I Made; Arihantana, Ni Made Indri Hapsari (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2019)
This research was aimed to identify the comparison effect of rice flour and purple sweet potato (Ipomoea batatas L. Poir) paste on the characteristics of cendol and to identify the right ratio of rice flour and purple sweet potato paste to produce cendol with the best characteristics. Completely randomized design was used in this research with treatment ratio of rice flour and purple sweet potato paste which consisted of 6 levels :  50% : 50%, 40% : 60%, 30% : 70%, 20% : 80%, 10% : 90%, and 0% : 100 %. Each treatment was repeated 3 times, resulting in 18 experimental units. The data were then analyzed with a nalysis of v ariance and if the treatment had an effect on the variable, the Duncan test was performed. The results showed that rice flour and purple sweet potato paste ratio had significant effect on water content, ash content, crude fiber content, antioxidant activity, anthocyanin , color, texture , flavor, taste , and overall acceptance of cendol . Making purple sweet potato cendol without using rice flour resulted the best characteristic under the following criteria: 89,47%  water content, 0,1 4 % ash content, 1,44% crude fiber content, 93,42 mg/mL antioxidant activity, 1,37 mg/100g  anthocyanin , dark purple and very liked color , texture chewy and liked, flavor typical of purple sweet potato and liked, taste very typical of purple sweet potato and liked, and overall acceptance very liked.   Keyword : cendol, purple sweet potato paste, rice flour